Kinetic Studies on the Non-isothermal Decomposition of Poly(methyl methacrylate) - Zeng, W.R.; Zong, R.W.; Yao, B. (Asian Journal of Chemistry, 2010)
The model-fitting method and iso-conventional method are used for studying the kinetic mechanisms of poly(methyl methacrylate) decomposition under nitrogen and air. The decomposition of poly(methyl methacrylate) in nitrogen has two mass loss stages, corresponding to the endchain scission model and the random chain-breaking model, respectively. The model-fitting results show that the decomposition rate of the first stage is controlled by diffusion process with average activation energy E of 158.5 kJ mol-1. The rate-limiting step of the second mass loss stage is the random chain-breaking reaction itself, which is a 1.5 order chemical reaction with average activation energy E of 214.79 kJ mol-1. In air, there are also two stages of mass loss for poly(methyl methacrylate) decomposition. The presence of oxygen restrains the decomposition of poly(methyl methacrylate) at the initial stage. The kinetic mechanism of the first mass loss stage is a first-order chemical reaction and the average activation energy E is 130.32 kJ mol-1. It suggests that the reaction rate of this stage is influenced not only by the decomposition of the stable peroxy radical but also by the diffusion or random chain-breaking process. In the second mass loss stage, the reaction mechanism is also a first-order chemical reaction with the average activation energy of 78.25 kJ mol-1. The transport-driven processes appear to dominate the rates of product formation. The relationship between the activation energy ‘Ea’ and extent of conversion ‘a’ of poly(methyl methacrylate) decomposition in air is obtained by the iso-conventional method. At initial stage, the activation energy ‘Ea’ is high and then decreases gradually as the extent of conversion ‘a’ increases. As a > 0.9, Ea decreases rapidly. The result is well consistent with that of model fitting method.